Kendali Optimal Model Prognosis Sindrom Metabolik Dengan Faktor Resiko Obesitas Dan Diabetes Melitus Tipe II Menggunakan Minimum Pontryagin - Nurannisa; Ratianingsih, R; Puspita, J W (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTMetabolic syndrome (SM) is a compound of risk factors of cordiovascular disease occurancy. Obesity and type IIdiabetes mellitus are the main two of the risk factors. The epidemiological data shous that the prevalence ofmetabolic syndrome in the world is 20-25%. The objective of these research is control to minimize the prognosisof the disease among the SM population that have obesity and type II DM risk factors. The pontryagin minimumprinciple is used to determine the optimal solution of the prognosis model that the optimal control. The solution is derived from the state and co-state state equations that are evaluated of the drug that give to the sufferer in stationary conditions. The performance Index was designed to minimize the number of SM population that suffer obesity and type II diabetes mellitus and the use of sulfonilurea that given as the normoweighted populations and biguanid for obese populations. The simulation of the optional solution shows that the optimal control was derived to control the number SM that have population of the optional solution obesity and type II DM risk with optimal biguanide 500 mg and sulfonilurea 5 mg as much.Keywords : Metabolic Syndrome, Minimum Pontryagin, Obesity, Stability ,Type II Diabetes Mellitus.